The sociocultural influences on maternal healthcare utilisation among adolescent mothers in Nigeria: a pooled data analysis - Alex-Ojei, Christiana Alake (My University, 2021)
Introduction: Adolescent pregnancy is a common occurrence in Nigeria, as nearly a quarter of girls aged 15-19 were either pregnant or had already given birth to at least one child in 2013. Studies have shown that pregnant adolescents have a higher risk of pregnancy morbidity and mortality compared to older mothers. To reduce the risks associated with adolescent pregnancy, adolescent mothers require antenatal, delivery and postnatal care to ensure that they and their children have good health outcomes. However, maternal healthcare utilisation in Nigeria has been lower for adolescent mothers than for mothers aged 20 and above. There needs to be an increased focus on access to and utilisation of maternal healthcare services for adolescent mothers if Nigeria is to meet the first, second and seventh targets of Sustainable Development Goal Three (SDG 3) to reduce maternal and child mortality, and ensure universal access to reproductive healthcare globally by 2030. While previous literature has focused on the sociodemographic and socioeconomic factors that are associated with adolescent maternal healthcare utilisation in Nigeria, little is known about the sociocultural factors that determine service use among these mothers. Therefore, the study examined the patterns of maternal healthcare utilisation and the influence of sociocultural factors on pregnancy experiences and service use among adolescent mothers in Nigeria. The specific objectives of the study were, (i) to examine the patterns of maternal healthcare utilisation among adolescent mothers, (ii) to investigate the pregnancy, intrapartum, and postpartum experiences of adolescent mothers, (iii) to identify the sociocultural barriers and enablers of maternal healthcare utilisation among adolescent mothers, and (iv) to examine the proximate factors that moderate the relationship between sociocultural factors and utilisation of maternal healthcare services by adolescent mothers in Nigeria. Theoretical Framework: The fifth revision of the Andersen Behavioural Model of Healthcare Utilisation (2008) was adopted as the study’s theoretical framework. In addition to previous revisions of the theory, the 2008 revision recognised that both individual and contextual prevailing, enabling and need factors determined healthcare use. Data and Methods: The study used the explanatory sequential mixed methods design. Quantitative data used were from the Women’s Recode dataset of the Nigeria Demographic and Health Surveys carried out in 2003, 2008 and 2013, which were pooled to achieve a weighted sample size of 3,260 adolescent girls aged 15 to 19. Qualitative data were collected using semi-structured in-depth interviews with fifty-five young mothers who had given birth when aged 19 or younger, and whose ages ranged from 15 to 22; nineteen of their own mothers or female guardians; and key informant interviews with six senior health workers and five female community leaders. For the qualitative study, respondents were drawn from urban and rural research sites in Ondo State in the South West zone, Katsina State in North West, and Imo State in the South East zone in Nigeria. Quantitative data were analysed at three levels. The univariate level involved computing frequency distributions of the sociocultural and sociodemographic attributes of adolescent mothers, as well as their maternal healthcare utilisation patterns. At the bivariate level, chi square tests were conducted to identify the variables which were significantly associated with maternal healthcare utilisation. At the multivariate level, binary and multinomial logistic regression analyses were conducted to identify the independent variables and covariates which were significantly associated with maternal healthcare utilisation among adolescent mothers in Nigeria. Qualitative data were analysed using a thematic analysis approach, whereby verbatim quotes from respondents were transcribed, grouped and interpreted according to themes identified after examining the data. Key findings: Objective 1: Patterns of maternal healthcare utilisation: The frequency distribution showed that the proportion of adolescent mothers made four or more antenatal care visits declined from 2003 to 2008, but increased in 2013. In 2003, 37.7% of adolescent mothers made four or more antenatal care (ANC) visits; in 2008, 33.1% made four or more ANC visits; and in 2013, 38.5% made four or more ANC visits. Proportions of adolescent mothers starting antenatal care early increased in 2008 from 2003, but declined in 2013. In 2003, 22.9% of adolescent mothers started ANC early; in 2008, 24.4% and in 2013, 21.8%. The proportion of adolescent mothers using skilled birth attendants (SBA) declined from 2003 to 2013. In 2003, 52.5% of adolescent mothers used SBAs during delivery. The figure declined to 34.6% in 2008, and 30.6% in 2013. The proportion of adolescent mothers using postnatal care (PNC) declined from 2003 to 2008 but increased in 2013. In 2003, 22.2% of adolescent mothers used PNC; in 2008, only 9.7% did, and in 2013, 21.1%. Findings from the bivariate analysis show that age of respondent, age at birth, educational level, religion, ethnicity, partner educational level, getting money for treatment, distance to health facility, place and region of residence were significantly associated with the number of antenatal care visits (p<0.05). Also, marital status, sex of household head, healthcare decision, partner age difference and getting permission to go to the health facility were significantly associated with the number of antenatal care visits (p<0.05). Religion, ethnicity, region of residence, and healthcare decision-making were significantly associated with the timing of the first antenatal care visit (p<0.05). Additionally, respondent’s age, educational level, wealth status, religion, ethnicity, partner’s educational level, distance to health facility, place and region of residence, and number of antenatal care visits were significantly associated with the type of birth attendant used by adolescent mothers at delivery (p<0.05). The type of birth attendant was also significantly associated with respondent’s marital status, sex of the household head, and getting permission to go to the health facility (p<0.05). Variables that were significantly associated with postnatal care were respondent’s age, educational level, wealth status, religion, ethnicity, partner’s educational level, distance to health facility, place and region of residence, number of antenatal care visits and type of birth attendant used (p<0.05). Also, marital status, sex of household head, healthcare decision-making, and getting permission to go to the health facility were associated with postnatal care use(p<0.05). Objective 2: Pregnancy, intrapartum and postpartum experiences of adolescent mothers: Adolescent pregnancy was common in all the study sites except the urban South East zone. Findings showed that stigma relating to unmarried pregnancy was common, and there was high reporting of pregnancies as unwanted by unmarried girls. A good number of adolescent mothers reported receiving social support in form of financial and emotional support from their families and community, and maternal support was especially important to unmarried mothers. Findings also showed that modern healthcare use was high among participants in the rural South West, urban and rural South East. There were reports of complementary healthcare use and patronage of traditional- and alternative birth attendants in the urban South West and urban and rural North West. Also, there were few reported accounts of negative health worker attitudes. Objectives 3 & 4: Factors associated with adolescent maternal healthcare utilisation: Adolescent mothers who could not obtain permission to go to the health facility had a significantly lower likelihood of making less than four, and four or more ANC visits, compared to those who could obtain permission [adjusted relative risk ratio (aRRR) =0.48; aRRR=0.65; p<0.05]. Findings from the qualitative study also showed that adolescent mothers sought antenatal care in situations where they could easily obtain permission to use the health facility. Also, having financial support was key to enabling adolescent mothers to seek antenatal care. Additionally, the qualitative data showed that healthcare preferences, and cultural and religious influences shaped antenatal care use among adolescent mothers. No sociocultural variables were significantly associated with timing of the first antenatal care visit by adolescent mothers. However, the qualitative data showed that the lack of family support, poor knowledge about sexual health and pregnancy symptoms and fear of stigma were some reasons for late antenatal care initiation. Adolescent mothers who lived in female-headed households were significantly less likely to use skilled birth attendants than those living in male-headed households (aRRR= 0.42, p<0.05). Qualitative data showed that the reasons for using certain types of birth attendants included the presence of financial support, personal and community healthcare preferences, cultural and religious beliefs, and health worker attitudes. Findings from the quantitative study showed that there were no sociocultural variables associated with postnatal care use. Findings from the qualitative study showed that use of postnatal care was more common in the North West zone than in the South West and South East zones. Also, personal healthcare preferences and partner permission were reasons for seeking postnatal care. Conclusion Adolescent mothers’ usage of antenatal care, delivery and postnatal care was low in Nigeria. Although there was limited evidence from the quantitative data to show that sociocultural factors influenced maternal healthcare use, findings from the qualitative data showed that social support, personal, family and community healthcare preferences, and religious and cultural traditions played a major role in adolescent mothers’ maternal healthcare use. Implications of findings Study findings showed that intervention programmes needed to engage adolescent mothers’ families and communities to provide proper support for them during pregnancy to enable them to use maternal healthcare. Also, interventions to increase maternal healthcare use among adolescent mothers in Nigeria must use approaches that take into account the different religious and cultural contexts in the country. Additionally, there should be the establishment of specific programmes of action for maternal healthcare for adolescent mothers. Frontiers for further research Future quantitative investigations may be conducted to test the association of social support and healthcare preferences on maternal healthcare utilisation. Also, further qualitative studies may examine the sociocultural factors shaping adolescent maternal healthcare utilisation in other localities in Nigeria, especially among the minority tribes. Future studies may also examine the factors contributing to unwanted pregnancy among adolescent mothers in Nigeria.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the award of PhD in Demography and Population Studies